Physiographic Characterization of Micro Watershed: a Case Study of Nau Campus - Surve, Nilam; Shrivastava, P. K.; Nayak, Dileswar; Wandre, Sarika (Indian Forester, 2015)
Watershed characterization of the existing micro watershed in Navsari Agricultural University was done so as to help in preparing an effective water management plan of various Research farms of the University. Field observations during monsoon and as per the layout plan of campus, four micro watersheds were demarcated and standard characterization procedure was adopted to make a comparative physiographic study. It was found the watershed 'B' has the largest area 240.8 ha, followed by watershed 'C' with an area of 109.25 ha. Due to large area and higher form factor of B and C; rectangular shape, there are high discharges from these two watersheds, which can be harvested and used for multipurpose uses. The bifurcation ration varies from 1.65 to 5.3, the highest value of bifurcation ratio was 5.5, in watershed A, which suggests structural control in the area and low permeability. Watershed A and C have been affected due to land use changes either due to more building / roads or soil sodicity in the fields. This is evident on ground as most of the buildings in residential area have been constructed and also due to ingress of sea water in the northern side has made the soils saline sodic with comparatively lesser permeability.